Best Answer

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4

(multiply x2 - 3 by x, and subtract the product from the dividend)

1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x

2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12

(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)

1. 4x(x - 3) = 4x2 - 12 = 4x2 - 12

2. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

🙏

🤨

😮

Q: What is x3 plus 4x2-3x-12 divided by x2-3?

Write your answer...

Submit

Related questions

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2

The inverse of a number is 1 divided by that number. So the inverse of x3 + 1 is 1/(x3 + 1).

(-x3 + 75x - 250) / (x + 10) = x2 - 10x - 25

2x2+7/x1

1.6667

That depends on whether or not 2x is a plus or a minus

Dividend: 4x4-x3+17x2+11x+4 Divisor: 4x+3 Quotient: x3-x2+5x-1 Remainder: 7

x3 /12 + 16x + c

x3+3x2+3x+2 divided by x+2 equals x2+x+1

== == Suppose f(x) = x3 + 3x2 - 2x + 7 divisor is x + 1 = x - (-1); so rem = f(-1) = 11

2x3 - 7 + 5x - x3 + 3x - x3 = 8x - 7

x3+3x2+6x+1 divided by x+1 Quotient: x2+2x+4 Remaider: -3

(X^3-27) divided by (x-3)

(x4 + y4)/(x + y) = Quotient = x3 - x2y + xy2 - y3 Remainder = - 2y4/(x+y) So, x3 - x2y + xy2 - y3 - 2y4/(x+y)

Anything plus 0 is itself, so x3 + 0 is x3.

x3-x2+5x-1 with remainder 7, which the final answer would be written as:x3-x2+5x-1+[7/(4x+3)]

3

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

x3 + 4x2 + x + 4 = (x + 4)(x2 + 1)

lim (x3 + x2 + 3x + 3) / (x4 + x3 + 2x + 2)x > -1From the cave of the ancient stone tablets, we cleared away several feet of cobwebs and unearthed"l'Hospital's" rule: If substitution of the limit results in ( 0/0 ), then the limit is equal to the(limit of the derivative of the numerator) divided by (limit of the derivative of the denominator).(3x2 + 2x + 3) / (4x3 + 3x2 + 2) evaluated at (x = -1) is:(3 - 2 + 3) / (-4 + 3 + 2) = 4 / 1 = 1

It could be x3 + 2x + 0It could be x3 + 2x + 0It could be x3 + 2x + 0It could be x3 + 2x + 0

(x + 4) / (x3 - 11x + 20) = (x + 4) / (x2 + 4x - 5)(x + 4) = 1 / (x2 + 4x - 5) = 1 / (x + 5)(x - 1), where x ≠ -4

forty-four

(xn+2-1)/(x2-1)

People also asked